2010
DOI: 10.1007/s10620-010-1412-1
|View full text |Cite
|
Sign up to set email alerts
|

Rate and Factors Affecting Treatment Uptake of Patients with Chronic Hepatitis C in a Tertiary Referral Hospital

Abstract: Current treatment uptake for CHC patients was suboptimal, as a large proportion of patients were either reluctant for treatment or not suitable for the current antiviral therapy. Multidisciplinary interventions are needed in the short term while alternative antiviral therapy is desired in the long term to overcome barriers to treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…). This concurs with previous experience that HCV treatment uptake is low even in specialist clinics . That said, the majority of patients who deferred treatment did so because of mild disease.…”
Section: Discussionsupporting
confidence: 91%
“…). This concurs with previous experience that HCV treatment uptake is low even in specialist clinics . That said, the majority of patients who deferred treatment did so because of mild disease.…”
Section: Discussionsupporting
confidence: 91%
“…Pegylated‐interferon alpha and ribavirin (PR) therapy have been the standard of care (SOC) for CHC for over a decade, with a suboptimal sustained virological response (SVR) of approximately 50% in genotype 1 (GT1) CHC patients . However, the uptake of treatment was only around 50% because of the presence of decompensated cirrhosis and concerns or intolerance to side effects …”
Section: Introductionmentioning
confidence: 99%
“…In this issue of the journal, Yan et al [12] reported their retrospective study to evaluate the treatment rate of CHC patients and examine the reasons for non-treatment in a tertiary referral center in Hong Kong. Of their enrolled 303 CHC patients, 138 (45.5%) patients received no antiviral therapy.…”
mentioning
confidence: 99%
“…Although PegIFN plus ribavirin is cost-effective for the initial treatment of CHC, it is not uncommon that the cost for anti-HCV therapy will lead to patients rejecting therapy, as 12.3% of patients were not treated as reported by Yan et al [12] owing to the strict criteria for full government reimbursed antiviral therapy. In Taiwan, a good example is that the cost of therapy is currently reimbursed by National Health Insurance for 24-48 weeks regimen according to the achieving RVR or not.…”
mentioning
confidence: 99%
See 1 more Smart Citation